THE EFFECTIVENESS OF THE FLIPPED CLASSROOM TECHNOLOGY IN TEACHING DATABASE COURSES IN HIGHER EDUCATION - Inobat G`aniyeva; Isomiddinov Ma`rufjon (TADQIQOTLAR, 2025)
Abstract This paper explores the effectiveness of the Flipped Classroom model in teaching Database courses within higher education. The study aims to determine how the integration of digital learning environments and active learning strategies influences students’ academic performance, engagement, and digital competence. The research was conducted at Qarshi State Technical University, where students were divided into control and experimental groups. The experimental group received instruction through the Flipped Classroom model, which combines pre-class video lectures and in-class collaborative problem-solving activities. The results revealed a significant improvement in students’ understanding of database concepts, motivation, and participation compared to the traditional teaching approach. The study concludes that the Flipped Classroom approach enhances digital competence and improves the overall learning outcomes in database education.